Rasionalitas Berkonsumsi dalam Ekonomi Islam - Mardyan Nugraha Ridhowati; Anton Bawono; Rina Rosia (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2026)
This study aims to analyze the rationality of consumption in Islamic economics. This study uses a qualitative method with a library research type. The results of this study began with a crisis of thought regarding the assumption of conventional rationality that fails to represent the complexity of human motivation as a rational and systematic homo economicus actor in pursuing personal interests to maximize economic profits. Islamic economic rationality emerged as a solution with the emergence of the concept of homo islamicus whose actions are based on law the Qur'an and sunnah Al-Hadith and guided by the values ​​of monotheism, trustworthiness, and justice. Islamic economists consider the concept of Homo Economicus not yet reflecting noble humans because it does not contain Islamic morals and teachings. Homo Islamicus provides a picture of human economic behavior in Islam that does not only prioritize personal interests but also pays attention to social and spiritual welfare. In fact, rationalism in Islamic economics is in line with the principle of Maqasid al-Shari'ah, namely maintaining the five main aspects of human life, namely aiming to maintain and preserve the Islamic religion, human rights, reason, descendants, and property.